2019
DOI: 10.3390/met9030317
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of a Thermally-aged Cast Duplex Stainless Steel by in Situ Tensile Test at the Service Temperature

Abstract: Z3CN20.09M cast duplex stainless steel (CDSS) has been used for primary coolant water pipes in pressurized water reactors due to its excellent mechanical properties. Such pipes operate at an elevated service temperature (~320 °C) and experience issues of thermal aging embrittlement. In situ tensile tests were conducted to investigate the deformation mechanisms of Z3CN20.09M CDSS after long-term thermal aging at 475 °C for up to 2000 h in both optical microscope and scanning electron microscope at 320 °C. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…For example, at the applied strain of 20%, the tensile stress is ~900 MPa for the unaged condition and ~1100 MPa for the aged condition for the tensile loading Both in Figures 8a and 8b, it can be concluded that the aged at 475 • C for the 2000 h condition has a higher value in tensile stress than the as received condition. Such phenomenon was also found in the real in-situ tensile experiments of this steel [9]. As the mechanical properties of the austenite phase remain the same after long-term thermal aging [8,34,36], such an increase seen in bulk behavior can be explained by the hardening of ferrite phase during the aging process [8,34].…”
Section: Stress-strain Behaviorsupporting
confidence: 76%
See 4 more Smart Citations
“…For example, at the applied strain of 20%, the tensile stress is ~900 MPa for the unaged condition and ~1100 MPa for the aged condition for the tensile loading Both in Figures 8a and 8b, it can be concluded that the aged at 475 • C for the 2000 h condition has a higher value in tensile stress than the as received condition. Such phenomenon was also found in the real in-situ tensile experiments of this steel [9]. As the mechanical properties of the austenite phase remain the same after long-term thermal aging [8,34,36], such an increase seen in bulk behavior can be explained by the hardening of ferrite phase during the aging process [8,34].…”
Section: Stress-strain Behaviorsupporting
confidence: 76%
“…In Figure 8, the simulated stress is higher than the tensile experiments conducted on the same material that was published before [5,9]. This can be explained by two reasons.…”
Section: Stress-strain Behaviormentioning
confidence: 79%
See 3 more Smart Citations